LEAGUE OF NATIONS AS A PREREQUISITE FOR THE FOUNDING OF THE UN: THE INTERNATIONAL LEGAL AND POLITICAL DIMENSION OF US PARTICIPATION - Pchelnikov, Daniel Kostiantyn (Public Management and Policy, 2025)
The collapse of the League of Nations and the subsequent establishment of the United Nations represent one of the most significant institutional transformations in the history of international relations. Born out of the devastating consequences of World War I, the League of Nations was envisioned as a universal organization aimed at ensuring peace through collective security and diplomatic cooperation. Despite these aspirations, the League failed to prevent major international crises and ultimately dissolved after the outbreak of World War II. Its structural weaknesses, lack of enforcement mechanisms, and the absence of key powers—most notably the United States—undermined its legitimacy and effectiveness. At the same time, the United States played a paradoxical role in this institutional evolution. Although President Woodrow Wilson was instrumental in designing the League’s foundational principles, the U.S. Senate rejected American membership, citing concerns over sovereignty and congressional authority in matters of war. Nevertheless, the United States emerged as a principal architect of the United Nations two decades later, promoting a more robust framework for international security in response to the failures of its predecessor. This study explores the multidimensional crisis of the League of Nations, focusing on the political, structural, and geopolitical factors that led to its demise. It also analyzes the transformation of international cooperation mechanisms, with particular attention to the United States’ shift from non-participation to leadership in global governance. By tracing the trajectory from Wilson’s idealism to the pragmatic institutionalism of the postwar period, this research aims to shed light on the foundational lessons that shaped the modern system of collective security embodied in the United Nations.